Validation of a SARS‐CoV‐2 RNA RT‐PCR assay for high‐throughput testing in blood of COVID‐19 convalescent plasma donors and patients. Issue 2 (9th November 2020) - Strasser, Erwin F.; Steininger, Philipp A.; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger
Abstract: Background: The frequency of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNAemia in blood donors is uncertain. Thus, assays for SARS‐CoV‐2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data. Study Design and Methods: The cobas SARS‐CoV‐2 dual‐target reverse transcriptase PCR (RT‐PCR) assay, licensed for respiratory swab SARS‐CoV‐2 RNA testing, was validated for detection of viral RNA in blood. For the validation panel, SARS‐CoV‐2–positive plasma samples were prepared by spiking SARS‐CoV‐2–positive respiratory specimens in negative human plasma. The 95% limit of detection (LOD95) was determined by probit analysis. For clinical validation, coronavirus disease 2019 (COVID‐19) convalescent plasma (CCP) donors and patients with COVID‐19 with a severe disease course treated in an intensive care unit (ICU) were included. Results: The validation of the SARS‐CoV‐2 RT‐PCR assay for blood demonstrated high sensitivity and specificity and intra‐ and inter‐assay precision and efficiency. The LOD95 for SARS‐CoV‐2 RNA was 5.0 genome copies/mL (95% confidence interval [CI], 3.3‐12 copies/mL) for target 1 and 4.3 genome copies/mL (95% CI, 2.9‐10 copies/mL) for target 2. In a cohort of 39 CCP donors with 66 CCP donations no SARS‐CoV‐2 RNA in plasma was detected. Screening of 25 blood samples of 19 ICU patients with COVID‐19 showed six positive results for SARS‐CoV‐2 RNA in at least one target of the assay. Conclusion: The SARS‐CoV‐2 RNA assay, only licensed for respiratory swabs, performed on a PCR system for high‐throughput testing, showed a good assay performance for blood testing.